Murder, Nonnegligent Manslaughter, and Spatial Autocorrelation in Mid-South Counties - Mencken, F. Carson (Journal of quantitative criminology, 1999)
In this paper we explore to what extent county murder and nonnegligentmanslaughter rates in the midsouth are spatially autocorrelated, usinga variety of spatial autocorrelation tests. The data are 3-year averages ofUCR murder and nonnegligent manslaughter rates from the 383 midsouthcounties. Moran's I statistics show a statistically significant amountof spatial autocorrelation in the murder and nonnegligent manslaughter ratesamong the 383 midsouth counties. G statistics, however, fail to detect aglobal pattern in this region. We also compute G _i statistics and localMoran's I statistics with these data and detect some patterns oflocalized spatial autocorrelation. We estimated and compared an MLE spatiallag model and an OLS model with constructs informed by socialdisorganization theory. The regression analysis failed to detect anysignificant spatial effects for the midsouth counties.